2012
DOI: 10.1210/jc.2012-2205
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Gastric Bypass Surgery on Female Reproductive Function

Abstract: Ovulation persists despite morbid obesity and the changes from bypass surgery. Reproductive function after surgery is characterized by a shortened follicular phase and improved female sexual function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
65
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(72 citation statements)
references
References 42 publications
4
65
0
3
Order By: Relevance
“…It has been reported that DHEA-S levels decreased significantly at the end of the 2 nd year when compared to initial levels and no significant differences were observerd at the end of the 1st year and between the first and second years (8). Legro et al (2012) in their study, reported that SHBG levels increased during the first month (p <0.001), testosterone levels decreased in the 3rd month (p = 0.002), estrogen levels decreased in 6th month (p = 0.03), and progesterone levels did not change significantly (17).…”
Section: Results Regarding Hormone Levelsmentioning
confidence: 95%
“…It has been reported that DHEA-S levels decreased significantly at the end of the 2 nd year when compared to initial levels and no significant differences were observerd at the end of the 1st year and between the first and second years (8). Legro et al (2012) in their study, reported that SHBG levels increased during the first month (p <0.001), testosterone levels decreased in the 3rd month (p = 0.002), estrogen levels decreased in 6th month (p = 0.03), and progesterone levels did not change significantly (17).…”
Section: Results Regarding Hormone Levelsmentioning
confidence: 95%
“…From a metabolic point of view, the improved insulin sensitivity was proved by the decrease in fasting insulin levels. With regard to the reproductive system, the restoration of regular menstrual cycles and ovulation were noticed [60].…”
Section: Surgical Treatment Of Obesity-bariatric Surgerymentioning
confidence: 99%
“…S. Palomba, оценивавший эффек-тивность прегестационного использования Мет-формина у женщин с синдромом поликистозных яичников и высоким риском осложненного тече-ния беременности, не выявил терапевтического эффекта препарата на основании результатов анализа 17 рандомизированных исследований, проведенных у такой категории пациенток [21]. Принимая во внимание подобные результаты, неудивительно, что медицинская общественность и комитеты, ответственные за разработку нацио-нальных рекомендаций в таких странах, как США [22] и Великобритания [23], занимают осторожную позицию в отношении использования Метформи-на при данной патологии.…”
Section: консервативные способы восстановления репродуктивного здоровьяunclassified
“…В 2012 г. R. S. Lergo предпринял попытку доказать, что снижение массы тела вследствие гастрошун-тирования по Ру приводит к улучшению репро-дуктивной функции [22]. Было установлено, что снижение массы тела не сопровождалось каки-ми-либо изменениями в эндокринных менстру-альных параметрах.…”
Section: хирургические методы леченияunclassified